1998
DOI: 10.1161/01.cir.97.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Versus Tested Antitachycardia Pacing in Implantable Cardioverter Defibrillators

Abstract: The results of this 200-patient prospective study comparing tested versus empirical ATP show high success (95% versus 90%) for VT termination, with low rates of acceleration. ATP is safe and very effective and should be programmed "on" in all patients regardless of the predischarge EP inducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
89
0
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(99 citation statements)
references
References 24 publications
3
89
0
7
Order By: Relevance
“…Because previous studies have shown 90% to 96% ATP success rates for VT with CLϾ320 ms, [2][3][4][5][6][7][8] and these data demonstrated an ATP success rate of †Results adjusted for the occurrence of multiple episodes in the same patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because previous studies have shown 90% to 96% ATP success rates for VT with CLϾ320 ms, [2][3][4][5][6][7][8] and these data demonstrated an ATP success rate of †Results adjusted for the occurrence of multiple episodes in the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,8 To successfully reset VT within the limit of ventricular refractory period, the pacing algorithm in this trial was set at a relatively nonaggressive 8 pulses at 88% VT CL, which yielded an acceleration rate of 4%. Although not desirable, this rate of acceleration compares favorably to previous studies that have shown acceleration rates between 7% and 18% for treatment of spontaneous rapid VT. 2,3 Given the greater success for FVT between 280 and 320 ms, it is possible that both success and acceleration could be improved by different CL cutoffs. The greatest danger may be that acceleration will lead to a rhythm refractory even to shocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that ATP was programmed empirically, the results also support prior observations that "tailoring" based on electrophysiology study of induced VTs is not necessary in most situations. 10 No clinical predictors of ATP success could be found. Diminished left ventricular ejection fraction slightly reduced efficacy but reached only marginal statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Fast VT (FVT, 188 to 250 bpm) is typically programmed to receive painful shock therapy even though ATP might be successful. More recently, high success and low acceleration rates for FVT were demonstrated in coronary artery disease patients 10,11 but in a nonrandomized fashion, so a comparison with shocks for safety and QoL was not performed. This trial examined the efficacy, safety, and QoL associated with treatment of FVT with ATP compared with shocks in a broad ICD population.…”
mentioning
confidence: 99%